Pollen and Foraminifera Approaches to Identify Sediment Sources In The River Mouth Mahakam East Kalimantan - Winantris, Winantris; Jurnaliah, Lia (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
The central role of Mahakam River in the construction of Mahakam Delta is to supply sediment from terrestrial to the river mouth. The river upstream comes from Mount Camaru and the downstream part terminate at Makasar Strait. The surrounding area of the river is overgrown by wet tropical flora that produces pollen. The existence pollen in river sediments as an indicator that sediment came from terrestrial, and foraminifera as an indicator that sediment came from marine. The ratio changes of pollen to foraminifera show that there were differences of sediment source supply. The study was conducted at the river mouth. A shallow core, 200 cm depth, composed of sand and mud and sandy mud, from it taken vertically 11 samples to be analyzed pollen and foraminifera. Sample preparation was using standard methods acetolysis. Meanwhile, sample preparation of foraminifera using Hydrogen Peroxide method. Pollen found at all samples, but foraminifera only found in 8 samples. The data indicating that sedimentation process in the mouth of a river not only gets sediment supplies from terrestrial but also from marine. The quantity of pollen and foraminifera varies vertically. The frequency of pollen much higher than foraminifera that indicates of source sediments dominance came from terrestrial which carried by Mahakam river current. Sonneratia caseolaris pollen continuously found in all samples. Stictogongylus vandiemensis is species foraminifera the most common that followed by Ramulina confossa, both of them come from the sea particularly from the shallow sea.